2000
DOI: 10.1063/1.481090
|View full text |Cite
|
Sign up to set email alerts
|

Photoexcitation and predissociation intensities of the c′ 1∑u+ (v=3 and 4), c 1∏u (v=3 and 4), and b′ 1∑u+ (v=10, 12, 13, and 15) states of N2

Abstract: Articles you may be interested inA femtosecond velocity map imaging study on B-band predissociation in CH3I. II. The 2 0 1 and 3 0 1 vibronic levels High-resolution millimeter wave spectroscopy and multichannel quantum defect theory of the hyperfine structure in high Rydberg states of molecular hydrogen H 2 Photofragment spectroscopy is applied to investigate perturbations in the photoexcitation and predissociation of excited singlet states of N 2 . Discrete rovibrational levels in the Rydberg states cЈ 1 ͚ u … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 39 publications
(100 reference statements)
5
34
0
Order By: Relevance
“…Recent work in our laboratory has shown that direct singlephoton excitation with a VUV laser from low rotational levels of N 2 (X 1 Σ g + ) produces only atoms N( 4 S) + N( 2 D) from reaction (2) 11.09-13.60 eV (91.17-111.78 nm) (Gao et al 2011b;Pan et al 2011;Song et al 2016). This observation is in agreement with the early studies (Helm & Cosby 1989;Walter et al 1993Walter et al , 2000 using visible laser excitation of higher rotational levels of the N 2 (a″…”
Section: Need For Branching Ratio Measurements Of Vuv Photodissociatisupporting
confidence: 81%
See 1 more Smart Citation
“…Recent work in our laboratory has shown that direct singlephoton excitation with a VUV laser from low rotational levels of N 2 (X 1 Σ g + ) produces only atoms N( 4 S) + N( 2 D) from reaction (2) 11.09-13.60 eV (91.17-111.78 nm) (Gao et al 2011b;Pan et al 2011;Song et al 2016). This observation is in agreement with the early studies (Helm & Cosby 1989;Walter et al 1993Walter et al , 2000 using visible laser excitation of higher rotational levels of the N 2 (a″…”
Section: Need For Branching Ratio Measurements Of Vuv Photodissociatisupporting
confidence: 81%
“…The D 0 (N 2 ) is 9.7537±0.0011 eV (127.12-0.02/+0.01 nm) (Tang et al 2005) and thus, there are three accessible energetically allowed dissociation channels (1)-(3), in the energy interval between 9.75-13.60 eV (91.17-127.12 nm): Previous photodissociation studies reported that reaction (1) is negligible (e.g., Helm & Cosby 1989;Walter et al 1993Walter et al , 2000. However, these studies involved high rotational levels of excited predissociative states of N 2 , whereas low rotational levels are of interest in astronomical environments.…”
Section: Need For Branching Ratio Measurements Of Vuv Photodissociatimentioning
confidence: 99%
“…1 wherever there is a near degeneracy of valence and Rydberg states. Rotational interactions are also known to mix the 1 u and 1 + u states, leading to energy-level perturbations near crossing points in their rotational progressions, and accompanying intensity interference effects [5,6,18].…”
Section: Introductionmentioning
confidence: 99%
“…1 The absorption is associated with dipole-allowed excitation of singlet ungerade ͑c n Ј 1 ⌺ u + , bЈ 1 ⌺ u + , c n 1 ⌸ u , o n 1 ⌸ u , and b 1 ⌸ u , where n is the principal quantum number͒ states, which are known to undergo strong predissociation, [2][3][4][5][6][7][8][9][10][11][12] some showing rotational dependence. 13 The rates of predissociation of these levels are key inputs in the radiation budget of the Earth's atmosphere, but the applicable predissociation mechanisms are far from being understood at present.…”
Section: Introductionmentioning
confidence: 99%
“…14 Lifetimes of the singlet ungerade states in N 2 have been measured using a wide variety of sophisticated experimental techniques. Laser-induced photofragment translational spectroscopy was performed in various studies 4,[6][7][8]10,12 that also provided direct information on the predissociation yields. Direct time domain studies have also been performed, either via the delayed coincidence technique combined with synchrotron radiation, 15 or via a vacuum ultraviolet-laser based pump-probe technique.…”
Section: Introductionmentioning
confidence: 99%